Pengaruh Reputasi Merek dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Miss U Project Wedding Planner Sukabumi - Mela Suranti; Mochamad Afrizal Maulana (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
The Indonesian wedding planning industry is growing rapidly, but Miss U Project Wedding Planner Sukabumi experienced a decline in customer numbers from 2021 to 2024, which raises questions about the extent to which brand reputation and service quality influence customer satisfaction. The research method used a quantitative approach with an associative design, involving the entire population of 74 respondents through a questionnaire that was tested for validity and reliability, then analyzed using multiple linear regression using SPSS 31. The results showed that 1) Brand reputation does not have a significant effect on customer satisfaction. 2) Service quality has a positive and significant effect on customer satisfaction. 3) Simultaneously, brand reputation and service quality significantly influence customer satisfaction at Miss U Project. These findings highlight that service quality is the primary factor in building customer satisfaction, while brand reputation is not a decisive factor in this context. This research contributes theoretically to the development of service marketing studies and provides practical implications for Miss U.